Proprotein convertase subtilisin and kexin type 9 in Sub Clinical Hypothyroidism as a Risk Factor for Cardiovascular Disease (Journal of Pharmaceutical Negative Results, 2022)
A subclinical hypothyroidism characterized by s excessive amounts of thyroid-stimulating hormone despite appropriate levels of free thyroxine and free triiodothyronine. Subclinical hypothyroidism is linked to a higher risk of coronary artery disease and its mortalities, as it is associated with increased atherosclerosis. The presented study aimed to evaluate serum Proprotein convertase subtilisin/Kexin type 9 level among patients with subclinical hypothyroidism. A cross-sectional study was conducted at Azadi Teaching Hospital in Duhok, Kurdistan Region-Iraq. The study was performed from November 2021 to January 2022. A total of 160 participants, including 80 patients with newly diagnosed subclinical hypothyroidism and 80 healthy subjects as a control group. Blood samples were taken from studied groups after overnight fasting for measurement of different parameters such as thyroid stimulating hommos, Free thyroxin, Free triiodothyronine, Anti-thyroid peroxidase antibody, Lipid profiles and Proprotein convertase subtilisin/Kexin type 9. A total of 160 participants were recruited in this study, 63(78%) of subclinical hypothyroid patients were females, and 48(60%) had a positive family history of hypothyroidism. The mean level of Proprotein convertase subtilisin/Kexin type 9. was significantly higher in subclinical hypothyroid patients in comparison with control (4.03±2.96, 2.74±0.96, p= <0.001), respectively. There was insignificant higher mean level of atherogenic indices, lipid profile and serum Proprotein convertase subtilisin/Kexin type 9 among subclinical hypothyroid patients with Thyroid stimulating hormones level of more than 7.00 IU/ml. In conclusion, our research revealed a statistically significant increase in the mean circulating levels of protein convertase subtilisin/kexin type 9 in individuals who had just been diagnosed with subclinical hypothyroidism.